CanSat, satellite in a soda can - Parusa, Jadug Norach Agna (2015)
Imparting space engineering skills and knowledge to interested individual have always been the main objective behind the CanSat competition. The first idea of such CanSat was proposed by Professor Bob Twiggs at “University Space Systems Symposium” in 1999 [1]. Afterwards, many universities and institutions have come out with new ideas and many different ways. They developed CanSat with various sizes and mission objectives, various sensors to collect many kinds of information, and various algorithm of autonomous landing system. CanSat stands for Can-Satellite. It is a miniaturized-satellite structure which size should be no larger than a soda can. It contains payloads and various sensors to gather surrounding information such as temperature, air-pressure, location data, and is to be launched from certain height (100s-meters). This structure will be attached with a parafoil to slow down the descending rate, in order to collect more data, control the landing, and reduce the hardware damage. And therefore, the choice of payload components inside the can would be significant to the successful development of CanSat.